2008
DOI: 10.1088/0004-637x/690/1/367
|View full text |Cite
|
Sign up to set email alerts
|

GALAXY CLUSTERS IN THESWIFT/BURST ALERT TELESCOPE ERA: HARD X-RAYS IN THE INTRACLUSTER MEDIUM

Abstract: We report the detection of 10 clusters of galaxies in the ongoing Swift/Burst Alert Telescope (BAT) all-sky survey. This sample, which mostly comprises merging clusters, was serendipitously detected in the 15-55 keV band. We use the BAT sample to investigate the presence of excess hard X-rays above the thermal emission. The BAT clusters do not show significant (e.g., 2σ ) nonthermal hard X-ray emission. The only exception is represented by Perseus whose high-energy emission is likely due to NGC 1275. Using XMM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
126
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(144 citation statements)
references
References 158 publications
16
126
2
Order By: Relevance
“…The HXR excess detection in Ophiuchus was recently confirmed by Nevalainen et al (2009). In addition, their joint INTEGRAL and XMM analysis partly reconciled the previous discrepancy between the results by Eckert et al (2008) and the upper limits on HXR flux obtained by Ajello et al (2009) through Swift/BAT data.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…The HXR excess detection in Ophiuchus was recently confirmed by Nevalainen et al (2009). In addition, their joint INTEGRAL and XMM analysis partly reconciled the previous discrepancy between the results by Eckert et al (2008) and the upper limits on HXR flux obtained by Ajello et al (2009) through Swift/BAT data.…”
Section: Introductionmentioning
confidence: 55%
“…8). We also added to the SED the upper limits at 74 MHz (VLSS) and 607 MHz (GMRT), as well as the Swift upper limit (Ajello et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Extended (several arcminutes in scale) hard X-ray emission (with so far weak evidence for a non-thermal component) has been observed (Rephaeli & Gruber 2002;Fusco-Feminano et al 2004;Rossetti et al 2004;Lutovinov et al 2008;Ajello et al 2009), as well as a prominent non-thermal radio halo (Giovannini et al 1993;Thierbach et al 2003). The latter is clear evidence for particle acceleration.…”
Section: Introductionmentioning
confidence: 96%
“…Analyzing INTEGRAL, ROSAT, and RXTE data, Lutovinov et al (2008) found that the global Coma spectrum is well fitted with a thermal model and the evidence for a hard excess is very marginal (1.6σ ). Ajello et al (2009) analyzed combined XMM-Newton and hard X-ray Swift-BAT spectra and even though they could not rule out the presence of non-thermal hard X-ray emission outside of their 10 region, within their field of view they found a good fit with two thermal models, with no need for a non-thermal component. Wik et al (2009) analyzed combined Suzaku Hard X-ray Detector (HXD-PIN) and XMMNewton mosaic spectra of a larger 34 × 34 region centered on the Coma cluster.…”
Section: Shocks and Non-equilibriummentioning
confidence: 97%